Treatment efficiency in skeletal Class II patients treated with the Jasper Jumper - A cephalometric evaluation - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2007)
Objective: To analyze the effects of the Jasper Jumper appliance during the treatment of skeletal Class 11 malocclusion. Materials and Methods: Lateral cephalograms and hand-wrist radiographs were collected from 45 Class 11 growing patients (22 boys, 23 girls). Three sets of records (initial, before Jasper Jumper, after Jasper Jumper) from 25 patients were compared with 20 control subjects of similar skeletal developmental stage. Mean age of the treatment and control groups were 11.83 years and 11.3 years, respectively. The data were analyzed by using paired t.tests. Results: The results demonstrated that the Jasper Jumper effectively corrected Class 11 malocclusion, but the changes were 80% dentoalveolar. The Jasper Jumper induced a clockwise rotation of the occlusal plane without much alteration in vertical dimension. Skeletally, the maxillary growth was restricted and pogonion moved forward, improving the profile. Conclusion: The Jasper Jumper appliance may be an effective method to improve both the skeletal imbalance and the profile in growing patients.
Keywords: Class II correction; Jasper Jumper; functional treatment; FUNCTIONAL APPLIANCE THERAPY; HERBST APPLIANCE; MALOCCLUSION; DIVISION-1; DENTITION